2016
DOI: 10.1259/bjr.20151057
|View full text |Cite
|
Sign up to set email alerts
|

Quantra™ should be considered a tool for two-grade scale mammographic breast density classification

Abstract: Objective: To assess the agreement between Quantra™ (Hologic Inc., Bedford, MA) and Breast Imaging Reporting and Data Systems (BI-RADS®) and the performance of Quantra at reproducing BI-RADS mammographic breast density (MBD) assessment. Methods: MBD assessment was performed using Quantra and BI-RADS. BI-RADS assessment was performed in two phases (1314 and 292 cases, respectively). Kappa was used to assess the interreader agreement and the agreement between Quantra and BI-RADS, and receiver-operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…A study by Ekpo et al concluded that Quantra is a useful tool to assess mammographic breast density into dense and non-dense categories, instead of 4 distinct categories. [ 22 ] This is similar to our study findings, that shows greater agreement between Quantra with readers when the density data were dichotomized. Although breast density assessment is purely subjective with the elimination of numerical percentiles as recommended by ACR-BIRADS 5th edition, the cut-off value can be applied to stratify dense from the non-dense breast when radiologists are in doubt.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Ekpo et al concluded that Quantra is a useful tool to assess mammographic breast density into dense and non-dense categories, instead of 4 distinct categories. [ 22 ] This is similar to our study findings, that shows greater agreement between Quantra with readers when the density data were dichotomized. Although breast density assessment is purely subjective with the elimination of numerical percentiles as recommended by ACR-BIRADS 5th edition, the cut-off value can be applied to stratify dense from the non-dense breast when radiologists are in doubt.…”
Section: Discussionsupporting
confidence: 91%
“…Also in contrast were the high Quantra density cutoffs of 19.5% and 20%, respectively, reported by the studies from India and Australia. 16 , 17 It is unclear why the different studies have such disparate cutoffs. One possibility may relate to race and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity (0.7737) corresponding to the best cutoff value represents, among patients classified as low density by the radiologist, the fraction of patients that were also classified by QUANTRA as low density. Five of the 6 other published studies, 16 18 , 20 , 23 plus the abstract of the unpublished study of Rafferty et al 21 reported sensitivity and specificity. Their sensitivities and specificities were uniformly higher than ours, with sensitivities ranging from 78% to 91% and specificities ranging from 77% to 92%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations